2003
DOI: 10.1177/10598405030190010501
|View full text |Cite
|
Sign up to set email alerts
|

A Mentoring Program for New School Nurses

Abstract: Until recent years, school nursing practice consisted mainly of screenings and first aid. However, the changing health, social, and emotional needs of children in the school setting have brought about an expansion of school nursing services. Now school nurses must not only perform routine first aid and screenings, but they must also carry out independent health assessments, monitor various medications, counsel students from troubled homes, collaborate with their educational partners, and complete numerous repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Mentoring is a common practice in K-12 education to promote professional development and supervision among school-based practitioners, such as teachers (Fairbanks, Freedman, & Kahn, 2000), school counselors (Peace & Sprinthall, 1998), and school nurses (Houghton, 2003). Mentoring relationships often involve coaching, collaborative work, and skill demonstration (Schwille, 2008), and research has reported some positive results of mentoring.…”
Section: Professional School Counseling In Missourimentioning
confidence: 99%
“…Mentoring is a common practice in K-12 education to promote professional development and supervision among school-based practitioners, such as teachers (Fairbanks, Freedman, & Kahn, 2000), school counselors (Peace & Sprinthall, 1998), and school nurses (Houghton, 2003). Mentoring relationships often involve coaching, collaborative work, and skill demonstration (Schwille, 2008), and research has reported some positive results of mentoring.…”
Section: Professional School Counseling In Missourimentioning
confidence: 99%
“…Mentoring nurses new to the school nurse environment may lead to an increase in their competency, confidence, and role clarification, especially in an environment where the minimum level of preparation for this specialty practice varies from state to state. Research suggests that school nurses who completed a mentoring program were less likely to feel isolated and dissatisfied with their career (Houghton, 2003).…”
Section: Implications For School Nursing Practicementioning
confidence: 97%
“…School nurses stand astride the professions of nursing and education. As a result of practicing across two frequently differing paradigms, school nurses may feel isolated, distant, and marginalized from the educational community in which they practice (Houghton, 2003); this is especially true with novice school nurses. Furthermore, the lack of professional respect from educators and nursing colleagues outside the realm of school nursing (Costante, 2002) contributes to barriers that impede the school nurses' ability to become fully integrated in the educational setting.…”
Section: Introductionmentioning
confidence: 95%
“…In contrast, the school nurse is isolated from nurse colleagues in a milieu where the primary purpose is education and not health. Houghton (2003) indicates that at the onset of their careers, school nurses may experience isolation, discomfort, and uncertainty regarding their responsibilities. These feelings may result in job dissatisfaction and withdrawal from the school setting.…”
Section: Marginalization Of the School Nursementioning
confidence: 99%
“…School nurses also must possess expertise in pediatric nursing, public health, and mental health. The nursing shortage exacerbates the problem of locating qualified school nurses according to Houghton (2003). Providing mentorship for novice school nurses through teaching, advising, and supporting them-ultimately benefits students and encourages successful school nurse practice and retention of nurses in the school nursing specialty (Houghton).…”
Section: Transition To School Nursingmentioning
confidence: 99%